SGLT2 inhibitors among patients with heart failure with preserved ejection fraction: a meta analysis of randomised controlled trials. (25th January 2023) - Jaiswal, V I K A S H; Ang, S O N G P; Hameed, M A H A; Chia, J I A E E; Kalra, K R I T I; Attia, A A; Kanakannavar, S S; Roy, S; Naz, S I D R A; Hugo Alvarez-Aguilera, V I C T O R; Sharma, P R A C H I; Jaiswal, A K A S H
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Sodium glucose co-transporter 2 (SGLT2) inhibitors have been recommended in the practice guidelines for the treatment of patients with heart failure with reduced ejection fraction, however their effects among patients with preserved ejection fraction has been debatable. Objective: We aim to evaluate the SGLT2 inhibitor effect among patients with HFpEF including DELIVER and EMPEROR-Preserved trials. Methods: We performed a systematic literature search using the PubMed, Embase, Scopus, and Cochrane libraries for relevant articles from inception until August 30th, 2022. Statistical analysis was performed by calculating hazard ratio (HR) using the random effect model with 95% confidence interval (CI) and probability value (P). Statistical significance was met if 95% CI doesn't cross numeric "1" and p <0.05. Results: A total of 4 studies with 30418 patients (15390 SGLT2 inhibitor vs 15028 placebo) were included in our analysis. The average age and percentage of females were comparable between groups, with a mean age of 68.3 years and 39.7% of females in the SGLT2 inhibitor group, whereas 67.7 years and 40.5% of females in the placebo group. Most common comorbidities among the SGLT2 inhibitor group included diabetes mellitus (78.8% vs 78.4%). Mean follow-up duration was 2.92 years. SGLT2 inhibitors reduced composite cardiovascular death or first hospitalisation for heart failure (HR, 0.82(95%CI: 0.75-0.89), P<0.001, heart failure hospitalisation (HR, 0.74(95%CI: 0.67-0.82), P<0.001) compared with placebo. However, all-cause mortality (HR, 0.97(95%CI: 0.89-1.06), P=0.54), and cardiovascular mortality (HR, 0.96(95%CI: 0.82-1.13), P=0.66) were comparable between the both groups on SGLT2 inhibitor and placebo. Conclusion: SGLT2 inhibitors reduced the risk of cardiovascular death and hospitalisation for heart failure. The results suggest patients with HFpEF have almost similar outcomes compared with previous studies on HFrEF. Hence SGLT2 inhibitors can be used among patients with reduced and preserved ejection fraction. Forest Plot